POTENSI AKAL MANUSIA DAN PEROLEHAN ILMU PENGETAHUAN DALAM PEMIKIRAN EPISTEMOLOGIS IBNU KHALDUN - Nasrullah, Amin (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2024)
Islamic epistemology places reason as a source of knowledge, alongside revelation. However, until now Muslims still have different views regarding the relationship between reason and revelation, especially regarding the function of reason. So it is important for the Islamic ummah to formulate a holistic epistemological conception and combine the two. Ibn Khaldun is a Muslim philosopher who has an epistemological conception, which explains the potential of reason and its position alongside revelation. This article aims to understand Ibn Khaldun's conception of reason, its potential in the acquisition of knowledge, and its existence in Islamic epistelogy. The study uses qualitative descriptive analysis through literary methods, by tracing Ibn Khaldun's thoughts from the Muqaddimah as a primary source, and other relevant books. The study results showed that the mind plays an important role in acquiring knowledge. Intellect is the potential to understand everything, acquire and develop knowledge. Science is the human ability to make analysis and synthesis as a result of the thinking process (af`idah). The thinking process takes place based on levels, which are divided into three: `aql tamyizi, `aql tajribi, and `aql nadhari. Based on that, science is divided into two categories: naqliyyah and aqliyyah science. Ibn Khaldun's conception of science is integral and relevant to the current situation of Muslims, especially in the context of Islamic education and the challenges of scientific development.